Wideband planar antenna with reconfigurable omnidirectional and directional radiation patterns. Issue 8 (1st April 2013) - Patron, D.; Piazza, D.; Dandekar, K.R.
Abstract : Proposed is a reconfigurable planar antenna that can generate omnidirectional and directional radiation patterns. The design has been tuned to resonate at 3.8 GHz and covers a bandwidth of several hundred MHz. Using RF switches, the antenna can generate five different radiation patterns: a single omnidirectional mode and four directional modes. Simulations and measurements were carried out and are in good agreement. The compact planar design, large operating bandwidth, and ability to create both omnidirectional and directional radiation patterns make this antenna suitable for small form factor wireless devices in next generation cognitive networks.